Ulighed for alle - Ulighedspersepktiver i neoliberalismen fra 1930'erne til i dag - Skov Andersen, Rasmus (Slagmark - Tidsskrift for idéhistorie, 2020)
By exploring the ways in which inequality has been represented in neoliberal ideology and how neoliberal views of inequality have changed, this article illuminates some essential discrepancies and contradictory beliefs in the neoliberal thought collective. The paper argues that the views of inequality underwent fundamental changes from the early neoliberals of the interwar period to the later neoliberals of the post-War era. These changes are in part understood by different conceptions of liberty, the relation between the state and the market, and beliefs about the public interest. The early neoliberals problematized the relation between inequality and power, which they saw as a potential threat to the credibility of the fundamental freedom rights upholding the democratic society. This changed with the late neoli- berals, for whom inequality became a value in itself, connected to liberal notions of competition, diversity, and progress. Inequality was now to be celebrated, repre- sented, and measured as a sign of the free society and the well-functioning market.